Evaluation of the clinical success of four different types of lithium disilicate ceramic restorations: a retrospective study - Sharo Abdulrahman; Constantin Von See Mahm; Ranjdar Talabani; Darwn Abdulateef (BMC, 2021)
Abstract Background/purpose How long do lithium disilicate restorations last before they fail? The aim of this study was to assess the success rate of four different types of restorations made from lithium disilicate. Materials and methods A total of 87,203 ceramic restorations, classified into four different types (inlay or onlay, veneers (Vs), single crowns (SCs), and fixed partial dentures (FPDs)), were used. All were made of lithium disilicate (IPS e.Max CAD) with Cerec Inlab CAD/CAM system (Sirona Dental Systems, Bensheim, Germany). They were reported by dentists and entered in the database of the private B&R Dental Center between March 2015 and June 2020 and assessed retrospectively up to a period of 5 years based on the following parameters: failure rate and cause of failures (ceramic fracture, debonding, marginal adaptation, color match, endodontic intervention, periodontal disease, and secondary caries). Failure distribution according to gender, arch, and teeth type was also evaluated. The time-dependent time-to-failure/complication and their differences were calculated in months according to the Kaplan Meier and log-rank tests. The Chi-squared test (p 0.05) was used to assess the variations in causes of failure rates between different restorations. Results Kaplan Meier test showed overall cumulative survival probability of lithium disilicate restorations for up to years was 85.08%. Inlay/onlay and Vs ceramic restorations showed highest cumulative survival probability (99.4%, 98.6, respectively). FPDs had the least cumulative survival probability (52.9%) which was significantly (P < 0.00001) higher than for other ceramic restorations using the log-rank test. Moreover, overall time-dependent time-to-failure/complication occurred after 52.373 months according to Kaplan-Meier (CI: lower bound: 51.875 months; upper bound: 52.871 months). Ceramic fracture in both FPDs and SCs (27.6% and 26.6%, respectively) and debonding in Vs (12.7%) were significant as the main reasons for failure (P = 0.000). The failure rate was significantly higher for the maxillary arch than the mandibular arch (P = 0.021). Fracture and marginal discrepancy were more frequent in the molar region (77.5% and 14.75%, respectively) and significantly higher here than in the anterior and premolar regions (P = 0.000). Conclusion The medium-term performance of lithium disilicate is ideal. Ceramic fracture was the most common cause of failure in SCs and FPDs. FPDs presented with the highest failure rate based on evaluation for up to 5 years.